Botswana’s Progress Toward Achieving the 2020 UNAIDS 90–90–90 Antiretroviral Treatment and Virologic Suppression Goals: Results of a Population-Based Survey - Gaolathe, Tendani (Lancet HIV, 2016)
BACKGROUND: Global HIV programs continue to experience challenges achieving the high rates of HIV testing and treatment needed to optimize health and reduce transmission. Botswana represents a useful “demonstration case” in assessing the feasibility of achieving the new UNAIDS targets for 2020: 90% of all persons living with HIV knowing their status, 90% of these individuals receiving sustained antiretroviral treatment (ART), and 90% of those on ART having virologic suppression (“90–90–90”). METHODS: A population-based random sample of individuals was recruited and interviewed in 30 rural and peri-urban communities from October 2013 to November 2015 in Botswana as part of a large, ongoing PEPFAR-funded community-randomized trial designed to evaluate the impact of a combination prevention package on HIV incidence. A random sample of approximately 20% of households in each of these 30 communities was selected. Consenting household residents aged 16–64 years who were Botswana citizens or spouses of citizens responded to a questionnaire and had blood drawn for HIV testing in absence of documentation of positive HIV status. HIV-1 RNA testing was performed in all HIV-infected participants, regardless of treatment status. FINDINGS: Eighty-one percent of enumerated eligible household members took part in the survey (10% refused and 9% were absent). Among 12,610 participants surveyed, 3,596 (29%) were HIV infected; 2,995 (83·3%) of these individuals already knew their HIV status. Among those who knew their HIV status, 2,617 (87·4%) were currently receiving ART (this represented 95% of those eligible for ART by current Botswana national guidelines, and 73% of all HIV-infected persons). We obtained an HIV-1 RNA result in 99·7% of HIV-infected participants. Of the 2,609 individuals currently receiving ART with a viral load measurement, 2,517 (96·5%) had HIV-1 RNA ≤400 copies/mL. Overall, 70·2% of HIV-infected persons had virologic suppression, close to the UNAIDS target of 73%. Results of three sensitivity analyses to account for possible uncertainty due to non-participation and under-representation of urban areas, revealed somewhat lower, but nevertheless remarkably high 90–90–90 coverage. INTERPRETATION: Botswana, a resource-constrained setting with high HIV prevalence, appears to have achieved very high rates of HIV testing, treatment coverage, and virologic suppression for those on ART in this population-based survey, despite the Botswana ART initiation threshold of ≤350 cells/mm(3). These findings provide evidence that the UNAIDS 90-90-90 targets, while ambitious, are achievable even in resource-constrained settings with high HIV burden. FUNDING: The United States President’s Emergency Plan for AIDS Relief (PEPFAR) through the Centers for Disease Control and Prevention (CDC).